Asymmetric hybrid capacitors based on activated carbon and activated carbon fibre-PANI electrodes - Salinas Torres, D. (2013)
Composites consisting of polyaniline (PANI) coatings inside the microporosity of an activated carbon fibre (ACF) were prepared by electrochemical and chemical methods. Electrochemical characterization of both composites points out that the electrodes with polyaniline show a higher capacitance than the pristine porous carbon electrode. These materials have been used to develop an asymmetric capacitor based on activated carbon (AC) as negative electrode and an ACF–PANI composite as positive electrode in H2SO4 solution as electrolyte. The presence of a thin layer of polyaniline inside the porosity of the activated carbon fibres avoids the oxidation of the carbon material and the oxygen evolution reaction is produced at more positive potentials. This capacitor was tested in a maximum cell voltage of 1.6 V and exhibited high energy densities, calculated for the unpackaged active materials, with values of 20 W h kg−1 and power densities of 2.1 kW kg−1 with excellent cycle lifetime (90% during the first 1000 cycles) and high coulombic efficiency.